Analysis of Phytoconstituents and Biological Activities on The Selected Medicinal Plants of Dolakha and Sindhualchowk District of Nepal - Subba, Bimala; Thapa, Susila (Journal of Institute of Science and Technology, 2018)
Phytochemical and biological activities of methanolic extract of seven plants viz. Scindapsus officinalis Schott. , Lepisorus loriformis, Nicotiana tabacum L., Clematis buchananiana DC., Astilbe rivularis D. Don, Potentilla fulgens Wall. ex Hook and Taxus wallichiana Zucc. were carried out. The brine shrimp bioassay showed that N. tabacum, A. rivularis, and P. fulgens were pharmacologically active. The antibacterial potential was studied against Staphylococcus aureus (gram positive bacteria) and Escherichia coli (gram negative bacteria) using Agar Well Diffusion Method. Roots of P. fulgens showed inhibition against gram positive bacteria while the rhizome of A. rivularis showed inhibition against both gram positive and gram negative bacteria. Antioxidant activity was evaluated by 2, 2-diphenyl-1-picryl hydrazyl (DPPH) free radical scavenging activity and ferric reducing antioxidant power FRAP assay. Both assays showed that P. fulgens has high antioxidant activities with (IC50 =15.57 ± 3.6) lower than standard ascorbic acid.  Journal of Institute of Science and TechnologyVolume 22, Issue 2, January 2018, Page: 140-147